IMPACT OF THE COVID-19 PANDEMIC ON THE COURSE OF ALLERGIC DISEASES - Zuzanna Michalik; Klaudia Kapelka; Stanisław Malik; Przemysław Paduch; Zofia Bułka; Joanna Mazur; Dawid Kłos; Duszan Leja; Klaudia Czech; Kaja Zdrojewska; Lena Apanowicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: The COVID-19 pandemic affected millions worldwide, especially those with chronic diseases. Both direct effects of SARS-CoV-2 infection and indirect consequences, such as restrictions and changes in healthcare access, significantly challenged daily life and disease management. Allergic diseases like atopic dermatitis (AD) and asthma were particularly vulnerable, as their course is highly influenced by biological and environmental factors.Aim: This study analyzes the impact of the COVID-19 pandemic on the course of AD and asthma, based on available scientific literature.Material and methods: A narrative review of current literature was conducted, focusing on studies examining the relationship between SARS-CoV-2 infection, pandemic restrictions, and the clinical course of atopic dermatitis and asthma. The review emphasized disease exacerbations, healthcare access, psychological factors, and the impact of pharmacological treatments.Results: Patients with AD experienced symptom exacerbations due to increased psychological stress, lifestyle changes, frequent use of detergents, and restricted access to care. For asthma, severe or poorly controlled disease increased the risk of adverse COVID-19 outcomes, while well-controlled asthma did not worsen prognosis. Inhaled corticosteroids (ICS) and biological therapies did not increase the risk of COVID-19 complications and may have offered protective effects.Conclusions: The COVID-19 pandemic worsened allergic diseases by increasing stress, reducing healthcare access, and changing lifestyles. Severe asthma raised the risk of poor outcomes, but well-controlled asthma did not. Inhaled corticosteroids and biologics were safe and possibly protective. Ongoing treatment and attention to psychosocial factors remain essential for managing allergic diseases during such public health crises.